2005
DOI: 10.1002/mds.20608
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease, stroke, and related epidemiology

Abstract: We investigated the prevalence of cerebrovascular disease and other comorbidities in Parkinson's disease (PD) patients compared to the general population. Five hundred PD patients were chosen randomly from one author's (A.H.R.) database. Age- and sex-matched controls were derived from 270 patients with essential tremor from the same database and from 490 patients in a general practitioner's database. Age, hypertensive status, smoking status, coronary artery disease, orthostatic hypotension, diabetes mellitus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…However no such association could be established in PDO cases. One epidemiological study which included general population, ET and PD cases, found that the incidence of stroke was similar in the three groups [39]. One autopsy study reported 13% vascular disease in all forms of PS [32].…”
Section: Resultsmentioning
confidence: 99%
“…However no such association could be established in PDO cases. One epidemiological study which included general population, ET and PD cases, found that the incidence of stroke was similar in the three groups [39]. One autopsy study reported 13% vascular disease in all forms of PS [32].…”
Section: Resultsmentioning
confidence: 99%
“…However, studies devoted to an exploration of stroke prevalence in PD patients showed inconsistent results [58,59,60] that would require confirmation in the future. The lack of evidence that cerebrovascular disorders contribute to motor and cognitive decline in PD patients may be explained by recent data on levodopa-induced sympathetic modulation, which reduced the burden of vascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical parkinsonian syndromes should be considered in the differential diagnosis of such cases, 122 as should overlap with other common disorders of ageing such as Alzheimer's and cerebrovascular disease. 123 Older patients may have less motor fluctuation and dyskinesia despite more rapid progression. 124 In contrast, the sub-type of tremor dominant PD is generally associated with a younger age at onset, 125 a more benign clinical course and preserved mental status.…”
Section: Sub-groups In Pdmentioning
confidence: 99%
“…124 In contrast, the sub-type of tremor dominant PD is generally associated with a younger age at onset, 125 a more benign clinical course and preserved mental status. 119,[120][121][122][123][124][125][126] Conflicting studies report that prominent tremor is associated with older age, 127 dementia 128 and to a lesser extent rapid disease progression. 128 Other data suggest few clinical differences between youngand old-onset PD, 129 although muscular stiffness and sensory symptoms may be a more common presentation in younger patients.…”
Section: Sub-groups In Pdmentioning
confidence: 99%